Analysis of the Anti-Radicalism and Terrorism Socialization Program on Students in Bandar Lampung Influence to Prevent and Overcome the Doctrines of Radicalism and Terrorism: Anti Radicalism and Terorism - Dian Herlambang; Raesitha Zildjianda; Amelia Anwar; Satrio Nur Hadi (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The increasing spread of cases of violence in the name of religion is now more visible, one of which is among students who have been indoctrinated to participate in radicalism and terrorism. Many students in Bandar Lampung in particular do not understand what radicalism and terrorism are. This is what causes many students to fall into radical/terrorist groups. Therefore, outreach is needed for universities in Bandar Lampung. The socialization aim to overcome the notion of radicalism and terrorism that has occurred among students in Bandar Lampung.The method of implementing activities includes steps, determining participants, determining service activities based on agreement, and providing socialization materials, feedback, identification exercises, questions, and answers. The anti-radicalism and terrorism outreach activities carried out are a form of prevention and control of terrorism and radicalism movements in universities, especially in Bandar Lampung. This socialization is also a form of defending the country and eradicating these ideas.